Verificação dos princípios lean construction em obras de habitação popular no município de Campo Mourão - Paraná - Costa, Jonas Leite (2014)
The present study has objective to verify if the Lean Construction tools are applied on popular housing construction works in the city of Campo Mourão, Paraná state. This work has qualitative approach with descriptive and exploratory purposes by using the multiple Case Studies procedure. To accomplish this study two companies, operating in the popular housing segment in the city of Campo Mourão, named company A and company B were analyzed. To verify the Lean Construction philosophy, interviews were conducted with employees of the Engineering and Human Resources sectors, using a questionnaire containing the eleven principles of Lean Construction proposed by Koskela (1992). The Good Practices of the companies were also verified through a semi-structured questionnaire, adapted from Saurin (1997). The completion of the study showed that even in an unstructured way, Lean Construction principles are applied in organizations, providing advantages for horizontal construction companies, such as minimizing waste and increasing productivity and, contributing to the continuous improvement of production processes. The literature presents studies related to the application of these principles in construction, however, there is still the need for applied research that integrate concepts developed by academia to business, as well as studies related to the application of Lean tools in popular housing works.